1987
DOI: 10.1113/jphysiol.1987.sp016406
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of two types of calcium channels in mouse neuroblastoma cells.

Abstract: SUMMARY1. Two types of voltage-sensitive calcium channels were identified and studied in the neuroblastoma cell line NIE-115. Calcium channel currents as carried by Ba2+ (50 mM) were recorded using the whole-cell variation of the patch-electrode voltageclamp technique.2. A transient (type I) inward Ba2+ current was evoked by a step depolarization from a holding potential of -80 mV to potentials more positive than -50 mV. The current amplitude became maximum around -20 mV.3. A depolarization to potentials more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
181
0
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(205 citation statements)
references
References 41 publications
23
181
0
1
Order By: Relevance
“…Firstly, it is harder to separate, in the slice, the sustained calcium current from the leak or residual outward current. Secondly, differences in temperature, 33 calcium concentration 41 and cell size predict the calcium current in the slice to be 10 times larger than in dissociated neurons, which is not the case. This discrepancy can be explained if we assume that current amplitude in the dissociated cells gives an indication of the maximum level of recruitment.…”
Section: Difference After Kindlingmentioning
confidence: 97%
“…Firstly, it is harder to separate, in the slice, the sustained calcium current from the leak or residual outward current. Secondly, differences in temperature, 33 calcium concentration 41 and cell size predict the calcium current in the slice to be 10 times larger than in dissociated neurons, which is not the case. This discrepancy can be explained if we assume that current amplitude in the dissociated cells gives an indication of the maximum level of recruitment.…”
Section: Difference After Kindlingmentioning
confidence: 97%
“…Early studies found that LVA channels were more sensitive to block by 50 -100 M nickel than HVA channels (124,152,298). Subsequent studies found that many neuronal T-type channels required Ͼ10-fold higher concentrations for block, with many studies reporting IC 50 values of ϳ300 M ( Table 2).…”
Section: Isolated Neuronsmentioning
confidence: 99%
“…The temperature sensitivity of T-type currents has been measured in thalamic neurons (85), DRG neurons (305), N1E-115 neuroblastoma cells (298), and GH 3 cells (343). Heating from 22 to 37°C caused over twofold increases in current amplitudes and accelerated channel activation and inactivation.…”
Section: Isolated Neuronsmentioning
confidence: 99%
“…The cobalt-permeable channels are probably not voltage-dependent Ca 2π channels, as several known voltage-dependent Ca 2π channel blockers had no effects on the accumulation of cobalt. In fact, cobalt itself is known to block voltage-dependent Ca 2π channels (Nachshen 1984;Narahashi et al 1987). The cobalt uptake procedure is largely used to detect the Ca 2π -permeable AMPA/ kainate receptors and reflects the Ca 2π entry through these receptors (Pruss et al 1991;Lu et al 1996).…”
Section: Discussionmentioning
confidence: 99%